Botulinum toxin A in the treatment of blepharospasm: a 10-year experience Toxina botulínica tipo A no tratamento do blefaroespasmo: experiência de 10 anos de utilização - Laura Silveira-Moriyama; Lilian R. Gonçalves; Hsin Fen Chien; Egberto R. Barbosa (Arquivos de Neuro-Psiquiatria)
To evaluate the long-term effect of botulinum toxin type A (BTX) in the treatment of blepharospasm, a retrospective analysis was conducted from the patients seen at the Movement Disorders Clinic of the Department of Neurology, Hospital das Clínicas, University of São Paulo School of Medicine from 1993 to 2003. A total of 379 treatments with BTX were administered to 30 patients with blepharospasm. Sixty six per cent of the subjects had used oral medication for dystonia and only 15% of them reported satisfactory response to this treatment. Ninety three per cent of the patients showed significant improvement after the first BTX injection. There was no decrement in response when compared the first and the last injection recorded. Adverse effects, mostly minor, developed at least once in 53% of patients. Six patients (20%) discontinued the treatment but there was no case of secondary resistance. Para avaliar os efeitos a longo prazo da toxina botulínica tipo A (BTX) no tratamento do blefaroespasmo foi realizado estudo retrospectivo no Ambulatório de Distúrbios do Movimento da Clínica Neurológica do Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo de 1993 a 2003. Um total de 379 aplicações de BTX foram administradas a 30 pacientes com blefaroespasmo. Previamente ao tratamento com toxina botulínica 63% dos pacientes utilizaram medicação oral para blefaroespasmo, mas apenas 15% referiu resposta satisfatória a este tratamento. Noventa e três por cento dos pacientes tiveram resposta significativa à primeira aplicação de BTX. Não houve decremento na resposta quando comparada a primeira à última aplicação registrada dos pacientes. Efeitos adversos, em sua maioria leves, ocorreram pelo menos uma vez durante o tratamento em 53% dos pacientes. Seis pacientes interromperam o tratamento, mas não houve nenhum caso de resistência secundária.